Path Dependence or Path Creation? - Garud, Raghu; Kumaraswamy, Arun; Karnøe, Peter (Journal of Management Studies, 2010)
abstractWe discuss the assumptions that underlie path dependence, as defined by Vergne and Durand, and then provide the outlines of an alternative perspective which we label as path creation. Path creation entertains a notion of agency that is distributed and emergent through relational processes that constitute phenomena. Viewed from this perspective, ‘initial conditions’ are not given, ‘contingencies’ are emergent contexts for action, ‘self‐reinforcing mechanisms’ are strategically manipulated, and ‘lock‐in’ is but a temporary stabilization of paths in‐the‐making. We develop these points using a narrative approach and highlight the theoretical and methodological implications of our perspective.